Facial expression of positive emotions in individuals with eating disorders. Issue 1 (30th November 2015) - Dapelo, Marcela M.; Hart, Sharon; Hale, Christiane; Morris, Robin; Lynch, Thomas R.; Tchanturia, Kate
Abstract: A large body of research has associated Eating Disorders with difficulties in socio-emotional functioning and it has been argued that they may serve to maintain the illness. This study aimed to explore facial expressions of positive emotions in individuals with Anorexia Nervosa (AN) and Bulimia Nervosa (BN) compared to healthy controls (HC), through an examination of the Duchenne smile (DS), which has been associated with feelings of enjoyment, amusement and happiness (Ekman et al., 1990 ). Sixty participants (AN=20; BN=20; HC=20) were videotaped while watching a humorous film clip. The duration and intensity of DS were subsequently analyzed using the facial action coding system (FACS) (Ekman and Friesen, 2003 ). Participants with AN displayed DS for shorter durations than BN and HC participants, and their DS had lower intensity. In the clinical groups, lower duration and intensity of DS were associated with lower BMI, and use of psychotropic medication. The study is the first to explore DS in people with eating disorders, providing further evidence of difficulties in the socio-emotional domain in people with AN. Highlights: We explored Duchenne smiles in women with anorexia (AN), bulimia (BN), and controls (HC). AN showed Duchenne smiles for shorter durations than BN and HC participants. AN participants' Duchenne smiles were less intense than those of BN and HC. Reduced Duchenne smile was related to low BMI, and use of medication. Results provide further evidence of difficulties in emotion processing in AN.